2003
DOI: 10.1117/12.485516
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the diffused aerial image model: an assessment based on multiple test cases

Abstract: Lithography modeling is a very attractive way to predict the critical dimensions of patterned features after lithographic processing. In a previous paper [1] , we have presented the assessment of three different simplified resist models (aerial image model, aerial image convolved with fixed gaussian noise and aerial image convolved with variable gaussian noise) by using a systematic comparison between experimental and simulated data. It has been shown that the aerial image convolved with fixed gaussian noise, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…to its simple analytical formulation. It has also been demonstrated in [7] that it predicts CD fairly accurately. This model assumes the printed contour can be computed by applying a constant bias to the contour where the intensity is equal to an intensity threshold I th .…”
Section: Algorithm 1 Kernel Decomposition and Table Generationmentioning
confidence: 92%
“…to its simple analytical formulation. It has also been demonstrated in [7] that it predicts CD fairly accurately. This model assumes the printed contour can be computed by applying a constant bias to the contour where the intensity is equal to an intensity threshold I th .…”
Section: Algorithm 1 Kernel Decomposition and Table Generationmentioning
confidence: 92%
“…CD and dose offsets are added that improve the accuracy of the simulations, and finally the DAIM uses only four parameters. A previous work [2] show that the DAIM is predictive and can simulate accurately CDs outside the set of data that have been used for fitting the model parameters. The DAIM coefficients depend of the whole resist process (resist thickness, layer stack, PAB, PEB, development conditions), and metrology conditions.…”
Section: Background: Model Description and Calibrationmentioning
confidence: 99%
“…This fit is based on functions that rely on physical considerations and that include the isofocal dose or threshold as explicit coefficients. [2] The four DAIM parameters are drawn together. All the masks and optical tools considered for the following work are considered as perfect (for process windows evaluation, it is highly improbable that non ideal objects would lead to improved process margins).…”
Section: Background: Model Description and Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In various publications, the validity of the diffused aerial image model ͑DAIM͒ was assessed. 8,9 It was concluded that DAIM is a good predictor not only for lines and spaces, but also for 2-D structures such as contact holes. The accuracy of DAIM was found to be comparable to full resist models.…”
Section: Introductionmentioning
confidence: 99%